1982
DOI: 10.1051/rnd:19820313
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenesis in the gonads of rainbow trout fry (Salmo gairdneri) before and after the onset of gonadal sex differentiation

Abstract: Summary. Gonadal Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(19 citation statements)
references
References 15 publications
1
16
1
1
Order By: Relevance
“…The basal levels of rtER mRNA are very similar to those found in the adult, and on Northern blot (result not shown) the presence of the two rtER mRNAs was noted. rtER and Vg genes also seem to be fully induced as early as at hatching and our results show that the estrogen response arises independently of sexual maturation which occurs later during development (Van den Hurk et al, 1982). These results are in good agreement with previous studies on chicken yolk Male rainbow trout (600-900 g) were injected with E, (1.5 mg/kg) or with the solvent.…”
Section: Discussionsupporting
confidence: 92%
“…The basal levels of rtER mRNA are very similar to those found in the adult, and on Northern blot (result not shown) the presence of the two rtER mRNAs was noted. rtER and Vg genes also seem to be fully induced as early as at hatching and our results show that the estrogen response arises independently of sexual maturation which occurs later during development (Van den Hurk et al, 1982). These results are in good agreement with previous studies on chicken yolk Male rainbow trout (600-900 g) were injected with E, (1.5 mg/kg) or with the solvent.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, in many species, testosterone seems to play an important role in sex differentiation and is closely related to gonadal differentiation [6,8,13,14,20]. In the present study, the testosterone peak observed at D30-D35 could be associated with the occurrence of sex differentiation in Eurasian perch [30], but as for other fish species, it was not possible to conclude if it is a cause or a consequence of gonadal differentiation [8,15,19,20]. The high levels of 11KT (median: 431.5 pg g À1 ) in mixed-sex groups and the lack of a detectable level in all-female batches suggest that this steroid was particularly important for male sex differentiation in Eurasian perch.…”
Section: Discussioncontrasting
confidence: 44%
“…These ''maternal'' sex steroids could be used as precursors to induce the initial sexual differentiation of the brain and/or the gonads. Sex steroid hormones are principally synthesized in gonad, although non-gonadal tissues, such as brain, blood, kidney or liver, can also synthesize these hormones [10,14,19,35]. The detection or presence of significant levels of testosterone, estradiol and 11keto-testosterone in embryos and developing larvae of Eurasian perch before the histological differentiation of the gonad strongly suggest an extra-gonadal synthesis of these sex steroid hormones in Eurasian perch, as has been observed in Coho salmon [8] and tilapia [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results together with ultrastructural (Oota and Yamamoto 1966;Van den Hurk et al 1982) and enzymocytochemical features (Van den Hurk et al 1982) indicate that interstitital steroidogenic cells are already functional in immature testes, and could be responsible for 17a20IOHP synthesis.…”
Section: Discussionmentioning
confidence: 58%